IMPLEMENTASI LAYANAN KONSELING ISLAMI INDIVIDU DAN KELOMPOK DENGAN PENDEKATAN ALQURAN - Randi Purnama (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
Islamic counseling in its implementation is the practice of Islamic teachings in accordance with the Qur'an and Sunnah or in other words fostering awareness to someone to carry out the activities of Islamic teachings. Islamic counseling in schools or madrasas is an alternative in helping, facing students' problems to become the character of Islam which refers to the Qur'an and Sunnah in accordance with Islamic teachings concerning the psychic of students. In addition, the Islamic counseling service aims to provide assistance to a person or group of people who are experiencing inner and outer difficulties in carrying out their duties as Abdullah (servant of Allah) and the Caliph on this earth in accordance with his nature and deliver it to be closer to Allah. and knowing who he is and strengthening the enforcement of monotheism within himself. the approach taken is guided by the Qur'anic verses, namely through counsel (QS Al Asr / 103: 1-3), through mau'izatul hasanah (QS Al-baqarah / 2: 10), mujadalah (QS, An-Nahl / 16: 125) and warnings (QS Adz-Zariyat / 51: 55). Implementation of individual and group Islamic counseling services is not far from counseling services in general, namely taking the following stages: planning, implementation, evaluation, analysis of evaluation results, follow-up, and reports.